2021
DOI: 10.18502/tbsrj.v3i1.6171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Diabetes Mellitus in β-thalassemia Major Patients in the North of Iran: Mazandaran β-thalassemia Registry - 2017 to 2019

Abstract: Introduction: Thalassemia is a hereditary hemolytic disease spread throughout India, Arabian Peninsula, Iran, Turkey, and Southeast Asia. Diabetes mellitus (DM) is a common complication of patients with β-thalassemia major (β-TM) due to iron sediment in the pancreas. The purpose of this study was to survey the prevalence of DM in patients with β-TM.   Material and Methods: Demographic, clinical information, and some biological tests in conjunction with the proportion of T2DM were retrieved from the Mazandaran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The hematopoietically active spleen may influence pancreatic islet cell immune death, making splenomegaly a risk factor for diabetes. [13,22] In children with β-thalassemia major, clinical signs of blood glucose imbalance may appear. Hepatomegaly from iron overload or hepatitis C infection, failure to thrive, thalassemic cardiomyopathy heart abnormalities, and desferrioxamine toxicity bone alterations are examples.…”
Section: Symptoms and Signsmentioning
confidence: 99%
“…The hematopoietically active spleen may influence pancreatic islet cell immune death, making splenomegaly a risk factor for diabetes. [13,22] In children with β-thalassemia major, clinical signs of blood glucose imbalance may appear. Hepatomegaly from iron overload or hepatitis C infection, failure to thrive, thalassemic cardiomyopathy heart abnormalities, and desferrioxamine toxicity bone alterations are examples.…”
Section: Symptoms and Signsmentioning
confidence: 99%
“…Several studies have suggested that males with β-thalassemia are more prone to develop diabetes relative to female counterparts. Studies in Turkey and Iran demonstrated that the prevalence of diabetes in β-thalassemia is higher in male patients 18 19 . A similar pattern was observed in the UAE, where thalassemic males had significantly higher serum ferritin levels, higher incidence of diabetes, and higher rates of cardiomyopathy relative to their female counterparts 44 .…”
Section: Introductionmentioning
confidence: 98%
“…1). Therefore, long-term monitoring and management are essential to delay or mitigate anemia, skeletal deformities, heart failure, and diabetes among other complications [18][19][20]. This article aims to review the evidence linking diabetes with β-thalassemia major and explore the utility of early prediction biomarkers and the mechanism(s) underlying this association.…”
Section: Introductionmentioning
confidence: 99%